An Efficient Labelling Approach to Harness Backbone and Side‐Chain Protons in 1H‐Detected Solid‐State NMR Spectroscopy. (11th November 2015) - Mance, Deni; Sinnige, Tessa; Kaplan, Mohammed; Narasimhan, Siddarth; Daniëls, Mark; Houben, Klaartje; Baldus, Marc; Weingarth, Markus
Abstract: 1 H‐detection can greatly improve spectral sensitivity in biological solid‐state NMR (ssNMR), thus allowing the study of larger and more complex proteins. However, the general requirement to perdeuterate proteins critically curtails the potential of 1 H‐detection by the loss of aliphatic side‐chain protons, which are important probes for protein structure and function. Introduced herein is a labelling scheme for 1 H‐detected ssNMR, and it gives high quality spectra for both side‐chain and backbone protons, and allows quantitative assignments and aids in probing interresidual contacts. Excellent 1 H resolution in membrane proteins is obtained, the topology and dynamics of an ion channel were studied. This labelling scheme will open new avenues for the study of challenging proteins by ssNMR. Abstract : Handfester Vorteil : Fraktionelle Deuterierung bei Festkörper‐NMR‐Spektroskopie mit 1 H‐Detektion liefert wichtige Informationen über austauschbare und nichtaustauschbare Protonen ohne Einbuße an spektraler Auflösung gegenüber Proteinen ohne nichtaustauschbare Protonen. Die Methode war erfolgreich für die Untersuchung von Membrantopologie und supramolekularen Wechselwirkungen eines Ionenkanals.